Alternating Voltage Introduced [001]-Oriented α-MoO3 Microrods for High-Performance Sodium-ion Batteries. (10th August 2017) - Li, Simin; Hou, Hongshuai; Huang, Zhaodong; Liao, Hanxiao; Qiu, Xiaoqing; Ji, Xiaobo
Abstract: Rod-like α-MoO3 is successfully designed by alternating voltage induced electrochemical synthesis (AVIES) approach. The morphology and texture of MoO3 is effectively controlled by applying various calcination temperature of 300–600 °C. Notably, the α-MoO3 microrods growing along [001] direction have the high aspect ratio, and the randomly stacked structure can facilitate the charge transfer and offer more active sites for sodium storage. When utilized for sodium-ion batteries, it presents the high charge capacities of 305 mAh g −1 at 1C and 143 mAh g −1 at 10C. Even after 3000 cycles at 10C, a significant capacity of 108 mAh g −1 is still delivered, highlighting its marvelous electrochemical properties. This work may be a compelling exploration for developing metal/metal oxides materials for sodium storages by AVIES.